(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Class III malocclusion is one of the most complicated orthodontic problems to diagnose & treat. There is a large phenotypic variation of this malocclusion. The purpose of this study was to observe the different characteristics of the malocclusion by cephalomertic analysis which will be useful for diagnosis and treatment planning of such cases. Materials and methods: This cross sectional descriptive study was conducted in the Department Orthodontics and Dentofacial Orthopedics, Dhaka Dental College. A total of 50 adult patients were selected. Cephalometric analysis was done by Steiner’s method. Data analysis was done by using micro soft office Excel 2007 program. Quantitative data were compared by student’s t-test. Results: Maxilla showed significant Prognathism (p= 0.0441) in relation to Class I norm. Mandibular Prognathism was also highly statistically significant (p=0.0001). The ANB value was significantly (p=0.0001) reduced in Class III adults. The mean of SND angle was significantly larger than class I norm (p=0.003). Mandibular plane was also found to be significantly (p=0.003) larger. Maxillary incisors were found to be protruded and mandibular incisors retruded significantly. Conclusion: Significant differences were observed in several Cephalometric characteristics in between class III malocclusion and class I norm of Bangladeshi adult population. JCMCTA 2022 ; 33 (2) : 43-48